Antara Syar'i dan 'Spill': Bagaimana Konten Dakwah Fashion di Media Sosial Membentuk Perilaku Konsumtif Mahasiswi Pendidikan Agama Islam? - Rohmatin, Alfa; Ridwan, Endan Hamdan; Gandara, Tedi; Permana, Diansyah; Masitoh, Imas (Politeknik Negeri Ambon, 2025)
Introduction: The proliferation of dakwah fashion content on social media, driven by influencers, has created a cultural paradox where Islamic values intersect with consumerism. While this phenomenon is assumed to influence purchasing decisions, its actual impact on individuals who are religiously educated remains empirically under-researched. This study aims to analyze the influence of social media usage intensity and dakwah fashion influencers on the consumption behavior of female Islamic Education (PAI) students in Indonesia. Methods: A quantitative approach was employed, using a total sampling method (census) to involve 50 active female students from the PAI program at STIT Al-Azami Cianjur. Data were collected through a structured questionnaire with a five-point Likert scale and analyzed using multiple linear regression, including classical assumption tests. Results: The statistical analysis yielded a counterintuitive yet significant outcome. The findings indicate that neither the intensity of social media usage nor the influence of dakwah fashion influencers had a statistically significant effect, either partially or simultaneously, on the students' consumptive behavior (p > 0.05). The model’s coefficient of determination (R-Square) was also extremely low, confirming a weak explanatory power. Conclusion and suggestion: This study concludes that female PAI students exhibit a form of